1999
DOI: 10.1001/archpsyc.56.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volume in Patients With Alcohol Dependence

Abstract: Background: Smaller hippocampal volumes have been reported in the brains of alcoholic patients than in those of healthy subjects, although it is unclear if the hippocampus is disproportionally smaller than the brain as a whole. There is evidence that alcoholic women are more susceptible than alcoholic men to liver and cardiac damage from alcohol. It is not known whether the hippocampi of the female brain are more vulnerable to alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
185
4
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(222 citation statements)
references
References 54 publications
21
185
4
11
Order By: Relevance
“…Prior structural neuroimaging studies in alcoholism have focused principally on global atrophic changes in cerebral cortex, white-matter, and cerebellum, plus local effects in hippocampus (62), demonstrating volume reduction (21)(22)(23)63). Smaller right amygdalae have been reported in relatives of alcoholics (56).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior structural neuroimaging studies in alcoholism have focused principally on global atrophic changes in cerebral cortex, white-matter, and cerebellum, plus local effects in hippocampus (62), demonstrating volume reduction (21)(22)(23)63). Smaller right amygdalae have been reported in relatives of alcoholics (56).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have indicated atrophic changes in amygdala and hippocampus in alcoholic subjects (21,22,55,56). Therefore, to further elucidate the sub-regions of these structures potentially impacted by alcoholism, we performed topological analyses using methods described in a previous report (54).…”
Section: Topological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Entry criteria for the present study were meticulous in their exclusion of subjects with substantial past or current alcohol or other substance abuse. The current sample may be less confounded, then, in terms of the possible influence of alcohol or drug abuse on hippocampal volume (Agartz et al 1999;Jernigan et al 1991;Sullivan et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although alcohol-related brain abnormalities are partially reversible with prolonged sobriety (Carlen et al, 1978;Gazdzinski et al, 2005;Mann et al, 1999;O'Neill et al, 2001;Parks et al, 2002;Pfefferbaum et al, 1995Pfefferbaum et al, , 1998Schroth et al, 1988), cortical gray and white matter may sustain long-term volume shrinkage and even loss (Jernigan et al, 1991;Pfefferbaum et al, 1992), especially in the prefrontal cortex (De Bellis et al, 2005) of older alcoholics (Cardenas et al, 2005;Pfefferbaum et al, 1997). Like amnesic patients with Wernicke-Korsakoff syndrome, non-amnesic alcoholics also have notable volume shrinkage of the mammillary bodies (Davila et al, 1994;Shear et al, 1996;Sullivan et al, 1999; but see Charness and DeLaPaz, 1987), anterior hippocampus (Agartz et al, 1999;Sullivan and Marsh, 2003;Sullivan et al, 1995), thalamus , and cerebellum (Sullivan et al, 2000a, b), but the volume shrinkage is substantially less than in alcoholics with WE or KS (cf, Blansjaar et al, 1992;Charness, 1993Charness, , 1999Mulholland et al, 2005;Sullivan, 2000). Because of the edematous nature of WE lesions, magnetic resonance imaging (MRI) methods sensitive to fluid changes in tissue have revealed bilaterally distributed hyperintensities in medial thalamus, mammillary bodies, and periaqueductal gray matter (eg, non-alcoholics: Chu et al, 2002;Doraiswamy et al, 1994;Unlu et al, 2006;Zhong et al, 2005) (alcoholics: Schroth et al, 1991).…”
Section: Introductionmentioning
confidence: 99%